As repercussões socioterritoriais da atividade de mineração no município de Barcarena estado do Pará - CHAGAS, Simone Franceska Pinheiro das (Universidade Federal do Pará, 2023)
: Our objective in this article is to analyze from the perspective of geography the debate that brings the New Mining Code (NCM). Our purpose is to critically reflect on the roleof mining within the Brazilian geographic space, where mining territories have different degrees of socio-environmental processes and conflicts. The central idea is to analyze the production model that exploits mineral resources on land use planning, and thus further instigatethe debate that has been made by society to think of another mining code, which in fact is sovereign and guarantees the Brazilian society the appropriation of wealth and the debate aboutwhat we want! What are our real interests? What does it mean to choose a type of economic exploitation that disregards society and its real interests? It implies the new mining code to interfere in the territories and impose a perverse deterritorialization on the interests of Braziliansociety, a savage territoriality. What is at stake in the new mining code by weakening the powerof the state to regulate mineral goods and to increase revenue, disregarding the real interests ofBrazilian society? These are essential issues in the debate about the use of territory, which we seek to analyze in this article.